Whole blood trace element and toxic metal concentration in dogs with idiopathic epilepsy and healthy dogs: A case-control study - Rosendahl, Sarah; Anturaniemi, Johanna; Kukko-Lukjanov, Tiina-Kaisa; Vuori, Kristiina A.; Moore, Robin; Hemida, Manal; Muhle, Anne; Hielm-Björkman, Anna (Frontiers in Veterinary Science, 2023)
Background: Idiopathic epilepsy (IE) is the most common neurological disease in dogs. Multiple genes and environmental factors interact to cause clinical signs, although the pathogenesis remains poorly understood. Extensive evidence from recent decades shows that trace elements play a role in epilepsy in humans, and recently it was shown for the first time that also dogs with IE have altered trace element status. On the other hand, toxic metals may cause seizures but research on their role in canine IE is lacking. Therefore, we aimed to investigate trace element and toxic metal concentrations in whole blood from dogs that had been diagnosed with IE and compare them to those of healthy dogs. Materials and methods: Whole blood concentrations of trace elements (selenium, zinc, copper, manganese, iron, and chromium) and toxic metals (arsenic, cadmium, mercury, and lead) were analyzed from 19 dogs that had been diagnosed with IE by board-certified neurologists and 19 healthy control dogs using inductively coupled plasma mass spectrometry. The concentrations in study and control group were compared using the Mann-Whitney U test. Results: Dogs diagnosed with IE had significantly higher blood copper concentration (P = .007), higher copper/zinc ratio (P = .04), and higher selenium concentration (P < .001), as well as lower chromium concentration (P = .01) when compared to healthy dogs. Treatment of IE with potassium bromide was associated with a significant elevation in blood arsenic concentration (P = .01). Conclusions: In conclusion, the present results support the role of altered trace element status in dogs diagnosed with IE and suggest that copper, selenium, and chromium may be involved in the pathogenesis of canine epilepsy or seizures. The results also suggest that potassium bromide may alter arsenic metabolism in dogs.